Cross Sectional, Seroprevalence Study of Peste des Petits Ruminants and the Related Risk Factors During Outbreak in Goats’ Farm in Egypt - El Bahgy, Halla E.K.; Abdelmegeed, Hala K.; Abdelwahed, Dina A.; Hassanien, Rabab T.; Afify, Ahmed F.; Kattab, Omnia M.; Shahein, Momtaz A. (Journal of Advanced Veterinary Research, 2023)
Peste des Petits ruminants’ virus (PPRV) is a notifiable transboundary and economically significant viral disease that affects goats and sheep. The current study was conducted to identify the seroprevalences of PPRV in goat farm in Marsa-Matroh province, Egypt during an outbreak in 2022. Moreover, this work aims to study the relevant risk factors directly related to the virus infection and attempt molecular characterization and phylogenetic analysis of the circulating strain. The samples included 356 sera, 154 nasal swabs, and 10 tissue samples were collected for PPRV screening and molecular characterization. The seroprevalence percent was found of 42.69%.Â It was observed that the prevalence rate, and case-fatality rate were higher under 6 months of age than in adults, and referring to sex, females had a more significant disease incidence than males. Based on phylogenetic analysis; the strains of the current study: PPR/AHRI-Matrouh1/Egy/2022 (accession number: OP881991) and PPR/AHRI-Matrouh2/Egy/2022 (accession number: OP881992) were identified as PPRV lineage IV, with 99.2% and 98.8% identity to the Ethiopian strain (Accession number MK571524) and Sudanese strain (Accession no HQ131931) respectively. An efficient PPR vaccination program with rigorous quarantine measures at the borders is advised to be implemented in the country to control the spread of the disease and avoid the entry of novel strains into the Egyptian governorates.